Lean Manufacturing- Toyota Production System (TPS) A Case of Dell - Yusoff, Farilah (2012)
Dell is one of the most highly rated PC companies and receives a lot of compliments for its products and customer service. On the internet, customers narrate a lot of pleasant experiences they had with Dell. One of customer who praises the Dell customer which they never had a problem with service Many users claim in their testimonials that all their PCs and printers are of Dell and are so satisfied that they have never needed to try any other . manufacturer. A large number of customers claim to be regular Dell customers and are greatly pleased with the fast delivery system and convenient return policy.